2017
DOI: 10.1371/journal.pone.0170623
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury Causes Blood-Brain Barrier Damage in Rats via Upregulation of Vascular Endothelial Growth Factor Expression

Abstract: Clinical manifestations of methylmercury (MeHg) intoxication include cerebellar ataxia, concentric constriction of visual fields, and sensory and auditory disturbances. The symptoms depend on the site of MeHg damage, such as the cerebellum and occipital lobes. However, the underlying mechanism of MeHg-induced tissue vulnerability remains to be elucidated. In the present study, we used a rat model of subacute MeHg intoxication to investigate possible MeHg-induced blood-brain barrier (BBB) damage. The model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 26 publications
2
21
0
2
Order By: Relevance
“…Other reporters [36] explained that the way of action of Me Hg induced neurotoxicity mediated through damaging of Blood-Brain Barrier (BBB) and alteration of calcium homeostasis and glutamate homoeostasis; moreover it helps in induction of apoptosis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other reporters [36] explained that the way of action of Me Hg induced neurotoxicity mediated through damaging of Blood-Brain Barrier (BBB) and alteration of calcium homeostasis and glutamate homoeostasis; moreover it helps in induction of apoptosis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mercury intoxication increases vascular endothelial growth factor expression, increasing BBB permeability (Takahashi et al 2017;Takahashi and Shimohata 2019). Actually, the etiology of brain mercury toxicity is the impairment of the BBB (Steinwall and Klatzo 1966;Steinwall and Olsson 1969;Takahashi and Shimohata 2019).…”
Section: Brain Mercury Accumulationmentioning
confidence: 99%
“…Studies have found mercury causes blood-brain barrier damage [89]. Once damaged, toxins can enter the brain with greater ease.…”
Section: Discussionmentioning
confidence: 99%